Udder edema in dairy cattle - Marçal, Wilmar Sachetin (Semina: Ciências Agrárias, 2006)
A review about Udder Edema is presented. The author describes the clinical forms and the most important etiologies recognized until now. Therapeutic and prophylatic conducts also are emphasized, including resolutions of management for heifers and cows to prevent other diseases of udder.